A critical analysis of law and practice of public private partnership in Tanzania: A case study of Kigoma District - Ndabhona, Iddi A. (Mzumbe University, 2024)
A dissertation submitted to Mzumbe University as a partial fulfillment of the requirement for the award of Master’s Degree of Laws in Commercial Laws (LL.M. CM) of Mzumbe University